La inteligencia emocional y su incidencia en el comportamiento de las niñas y niños del primer año de educación básica de la escuela fiscal “Pichincha” del cantón Santo Domingo, provincia de los Tsáchilas. Periodo lectivo 2014-2015”. Lineamientos alternativos - Campoverde Campoverde, Isabel Lucrecia (2015)
This thesis refers to "EMOTIONAL INTELLIGENCE AND ITS IMPACT ON THE BEHAVIOR OF THE CHILDREN OF THE FIRST YEAR OF BASIC EDUCATION SCHOOL TAX" Pichincha "CANTON SANTO DOMINGO, PROVINCE OF ECUADOR. School period 2014-2015 ". Alternative guidelines, the central problem is defined: How Emotional Intelligence affects the behavior of the children's first year of basic school education tax "Pichincha" Canton Santo Domingo province ECUADOR. School period 2014-2015? He was raised as General Objective: To raise awareness about the Master ranging from pre importance of Emotional Intelligence in the behavior of children from the first year of basic education. The methods used for the preparation of this research work were: Scientific, inductive-deductive, analytic-synthetic, Descriptive and Statistical Model, the same that served effectively help to achieve the proposed goal. The techniques and instruments used were: a survey of teachers First Year Basic Education school tax "Pichincha" to establish whether teachers develop emotional intelligence through its component on girls and children with a Behavioral Test (eBee León Gross) applied to the children of the first year of basic school education tax "Pichincha" to assess the behavior. It is concluded that: 100% of the surveyed teachers, believe that the most important components of emotional intelligence are: self-awareness, self-regulation and motivation; and, 67% social activities and empathy. Test results Behavioral (eBee León Gross) aimed at children determine that: 75% of children gained predominance in the response B equivalent to a Assertive, 17% obtained a predominance in the response C equivalent a passive behavior; and 8% had a predominance in the Answer equivalent to aggressive behavior.